1990
DOI: 10.1080/02786829008959404
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Kinetic Energy Loss for Particles Impacting Surfaces

Abstract: Incoming and rebounding particle velocities were measured to within several particle diameters of the impaction surface using laser Doppler velocimetry. Impacts occurred normal to the surface and ranged from 1 m / s , near the threshold for particle hounce, to 100 m/s, well into the plastic damage regime. Monodisperse ammonium fluorescein spheres, 2.6-6.9 p m in diameter, impacted target surfaces including polished molybdenum and silicon, cleaved mica, and a fluorocarbon polymer. The incident kinetic energy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
155
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(174 citation statements)
references
References 26 publications
15
155
0
4
Order By: Relevance
“…Hence the asymptote has a value of (k p /k e ) 1/2 [14]. This asymptotic behaviour is not in line with the experimental evidence [27,28], where it is shown that at sufficiently high velocity the impact energy far exceeds the adhesion energy and the coefficient of restitution is primarily a function of the energy loss due to plastic deformation.…”
Section: Comparison Of the Proposed Model With That Of Thornton And Nmentioning
confidence: 77%
See 1 more Smart Citation
“…Hence the asymptote has a value of (k p /k e ) 1/2 [14]. This asymptotic behaviour is not in line with the experimental evidence [27,28], where it is shown that at sufficiently high velocity the impact energy far exceeds the adhesion energy and the coefficient of restitution is primarily a function of the energy loss due to plastic deformation.…”
Section: Comparison Of the Proposed Model With That Of Thornton And Nmentioning
confidence: 77%
“…In order to define the dynamics of the process, the dimensionless shear strain rate,γ , of Tardos et al [29] is evaluated using Eq. (27), (27) where γ is the shear strain rate, d p is the mean particle diameter and g is the gravitational acceleration. The strain rate of 0.28 s −1 provides a dimensionless shear strain rate of ∼0.003.…”
Section: Sensitivity Analysis Of the Proposed Model Parametersmentioning
confidence: 99%
“…However, three of those experiments seem to have some relevance for astrophysical applications. The work of Wall et al (1990) deals with a variety of target materials including silicon. These authors used quite small spheres down to 2.58 km diameter.…”
Section: Previous W Ork On Small-particle Collisionsmentioning
confidence: 99%
“…Physical properties of particles, such as hygroscopicity, size, density, phase, elasticity, and hardness, play an important role in particle bounce behavior (Wall et al 1990;Stein et al 1994;Matthew et al 2008;Virtanen et al 2010;Virtanen et al 2011;Bateman et al 2014). Hygroscopic particles, such as salts, are known to have much less bounce than non-hygroscopic particles (Stein et al 1994).…”
Section: Introductionmentioning
confidence: 99%